Acute Conus Medullaris Syndrome Following Minimally Invasive Lumbar Discectomy: A Case Report with Narrative Review - Ibrahim, Bilal; Ibrahim, Bilal; Arabyat, Abdallah; Y. Hiasat, Mohammad; Nadi, Mustafa; F. Dabbas, Waleed (Journal of Neonatal Surgery, 2025)
Introduction:Lumbar disc herniation is a common cause of low back pain, often managed surgically via discectomy. While generally safe, discectomy may result in rare but serious complications such as conus medullaris syndrome (CMS). Most reported cases of CMS develop days to months postoperatively due to mechanical compression or vascular anomalies. Immediate-onset CMS without radiological abnormalities is exceptionally rare. Case Presentation:We report the case of a 43-year-old man who developed acute CMS following an uneventful L3/L4 tubular microdiscectomy that occurred within hours. The symptoms were bilateral foot drop, saddle anesthesia and urinary retention. On urgent MRI, the conus medullaris was free of any compressive lesions or signal changes. Clinical follow-up showed a dramatic improvement in neurological status of the patient. Conclusion:This case provides evidence to transient microvascular ischemia that may be involved in acute CMS presentation without radiologic abnormalities. Prompt clinical identification, use of perfusion imaging, and hemodynamic support may enhance outcomes in similar presentations.